Pengaruh Intellectual Capital dan Struktur Kepemilikan terhadap Return On Asset (Roa) Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2010-2014 - Dedy Supriyadi; F. Defung; M. Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The Purpose  of  this  study  is  to  analyse  the  relationship  between Intellectual capital using Pulic Models ( Value Added Intellectual capital Coefisien VAICTM) and Ownesrship Structure that are Managerial Ownwership and Institusional ownership on Return on Asset (ROA). Data from this study were obtained from financial statements and annual reports of Manufacturing Companies drawn from the Indonesia stock exchange. The object of this study is Manufacturing Companies listed on Indonesia stock exchange during the years 2010-2014 for 141 Companies. The type of data use are secondary data in the form of annual reports published by Manufacturing Companies. The method of analysis used in this study is multiple regression with SPSS Computer program. The result shows that Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Managerial Ownership have positive and significant influence on Return on Asset (ROA). Meanwhile the Structural Capital Value Added (STVA) and Institusional Ownership have no significant influence on Return on Asset (ROA).Keywords:       Value  Added  Capital  Employed  (VACA),  Value  Added  Human Capital (VAHU), Structural Capital Valu Added (STVA), Managerial Ownership, Institusional Owneship, and Return on Asset (ROA)